The Effect of Discounts and Service Quality on Customer Satisfaction at J&T Express Probolinggo Branch - Hermawan, Dedi Joko (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect between the variables of price discounts and service quality on customer satisfaction, as well as the effect of price discounts and service quality together on customer satisfaction. the type of data used in this study is quantitative data. The population in this study were J&T Express customers in the Probolinggo branch. The sample method used is non probability sampling and through incidental sampling techniques, the sample that was successfully collected was 30 respondents. The research methods used are validity test, reliability test and hypothesis testing. The results of this-study indicate that-the discount variable has no effect on customer satisfaction, the service quality variable affects customer satisfaction, and the discount variable and service quality jointly affect customer satisfaction.